The Population Impact and Cost-Effectiveness of Statins for Primary Prevention in Adults 75 and Older in the United States - Odden, Michelle C. (Ann Intern Med, 2015)
BACKGROUND: Over 40% of adults 75 and older are taking statins, yet there is little evidence to guide primary prevention in this population. OBJECTIVE: To project the population impact and cost-effectiveness of statin therapy in adults aged 75 years and older. DESIGN: Forecasting study using the Cardiovascular Disease Policy Model, a Markov model. DATA SOURCE: Trial, cohort, and nationally-representative data sources. TARGET POPULATION: U.S. adults aged 75–94 years. TIME HORIZON: 10 years. PERSPECTIVE: Health care system. INTERVENTION: Statins for primary prevention based on: 1) Low density lipoprotein cholesterol ≥4.91 mmol/L (190 mg/dL), 2) ≥4.14 mmol/L (160 mg/dL), 3) ≥3.36 mmol/L (130 mg/dL), 4) diabetes, 5) 10-year risk score ≥7.5% (treat all). OUTCOME MEASURES: Myocardial infarction (MI), coronary heart disease (CHD) death, disability adjusted life years, costs RESULT OF BASE-CASE ANALYSIS: All adults aged 75 and older in NHANES have a 10-year risk score >7.5%. If statins have no effect on functional limitation or cognitive impairment, all primary prevention strategies would prevent MIs and CHD deaths and be cost effective. The broadest strategy, treatment of all adults aged 75–94 years would result in 8 million additional users, and prevent 105,000 (4.3%) incident MIs and 68,000 (2.3%) CHD deaths at an incremental cost per disability adjusted life year of $25,200. RESULT OF SENSITIVITY ANALYSIS: An increased relative risk of functional limitation or mild cognitive impairment in the range of 1.10 to 1.30 could offset the cardiovascular benefits. LIMITATIONS: Limited trial evidence targeting primary prevention in adults 75 and older. CONCLUSIONS: At effectiveness similar to trial findings, statins are projected to be cost-effective for primary prevention in adults age 75–94 years; however, even a small increase in geriatric specific side effects could offset the cardiovascular benefit. Improved data on the potential benefits and harms of statins are needed to inform decision-making.